Abdominal Binder for Improving Postoperative Physical Function after Benign Gynecologic Surgery: A randomized controlled trial - Kornsakul Boonploeng; Somsak Pratipanawatr; Thumwadee Tangsiriwatthana (The Royal Thai College of Obstetricians and Gynaecologists, 2021)
Objectives: To compare physical functions by six-minute walk test (6MWT) between participants using postoperative abdominal binder versus routine postoperative care.Materials and Methods: Sixty participants undergoing benign gynecologic abdominal surgery were enrolled in a randomized controlled trial. The participants were randomized by a 1:1 ratio by computer-generated randomization using blocks of four to receive abdominal binder 2 hours after operation or received routine postoperative care, then 6MWT was performed on postoperative day 1 and day 2 in both groups. The primary outcome included improving walking distance. Visual analog scale (VAS) was used to measure pain levels at 6, 24 and 48 hours after surgery. Participants' characteristics, postoperative diagnosis and blood loss were assessed by medical record review. Results: 6MWT following surgery of both groups was statistically significant on day 1 with mean difference of 27.53 meters (95% confidence interval (CI): 0.95-54.11), p = 0.043 and day 2 with a mean difference of 71.77 meters (95%CI: 43.11-100.42), p < 0.001. In terms of walking distance, the experimental group could walk farther than control group. VAS scores at different time points (p < 0.001) and time of first postoperative ambulation were significant lower (p < 0.001) in abdominal binder group. There was no adverse event reported.Conclusion: Using postoperative abdominal binder can improve postoperative ambulation.